EFEKTIVITAS PENGGUNAAN APLIKASI GEOGEBRA PADA PEMBELAJARAN MATEMATIKA - Faradiba Jabnabillah Jabnabillah; Mahfudz Reza Fahlevi (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
Based on the results of observations in the field found several problems faced by SMK Putra Jaya School Batam, namely the depiction of graphs on the blackboard that is inaccurate so that it is difficult for students to understand, teachers have never used ICT-based learning media in learning mathematics, students are less interested in learning mathematics, the increasing number of mathematical materials that require students to be able to understand graphs of functions, plane shapes, geometric shapes, equations etc. This can be overcome in GeoGebra. As for what is analyzed in this study is the effectiveness of student responses and student learning interest in using the GeoGebra application. The method in this study was observation and a questionnaire consisting of two, namely the student response questionnaire in using the GeoGebra application and students' learning interests. Data analysis techniques use quantitative to measure the percentage of student responses and student interest in learning mathematics. The results showed that the students' responses were said to be very effective with a percentage of 82% and the percentage for interest was 80%. This effectiveness is seen from interesting view of the application and ease of using the application which makes students at SMK Putra Jaya School happy and interested in learning mathematics.